2013
DOI: 10.1039/c2ra21963h
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of surfactants towards CdS nanoparticles: synthesis, stability, optical and PL emission properties

Abstract: a Cadmium sulfide (CdS) nanoparticles (NPs), prepared by a convenient chemical precipitation method, have been characterized using techniques such as TEM, XRD, zeta potential, absorption and photoluminescence (PL) emission spectroscopy to establish the structure directing role of different cationic and anionic surfactants and their impact on the nanoparticles stabilization. In the synthesis of the CdS NPs, cadmium acetate and sodium sulfide, employed as starting reagents, were dissolved in aqueous solutions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…The effectiveness of the cationic and anionic surfactants in controlling the shape and size of CdS NPs has been successfully established in our earlier reports [24,25]. The Zeta potential measurements established that the NPs has been stabilized through head group adsorption of surfactants over the NP's surface and stabilization tendencies of the surfactants have been mainly governed by the hydrophobic chain length.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The effectiveness of the cationic and anionic surfactants in controlling the shape and size of CdS NPs has been successfully established in our earlier reports [24,25]. The Zeta potential measurements established that the NPs has been stabilized through head group adsorption of surfactants over the NP's surface and stabilization tendencies of the surfactants have been mainly governed by the hydrophobic chain length.…”
Section: Resultsmentioning
confidence: 93%
“…It has already been established that the surfactant molecules interact with surface of CdS NPs and thereby modulate their emission properties [24,25]. The changes in emitting states of CdS NPs during growth and/or adsorption of surfactants can be useful in understanding the origins of PL properties.…”
Section: Steady-state Pl Properties Of Growing Cds Npsmentioning
confidence: 98%
See 1 more Smart Citation
“…Absolute Z potential values above 30 mV provide good stability, because at these conditions, nanoparticles tend to repel each other. 24 This behavior is due to the adsorption of ions at the nanoparticle surface. The Z potential values for AuNPs synthesized with ascorbic acid and sodium citrate without pectin were À19.50 and À0.058 mV, respectively, far below the stability limit, which explain the growth and agglomeration observed in UV-vis and TEM.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the surfactant-solvent interactions may significantly affect the optical properties of CdS nanoparticles [26,27]. Reaction mechanism and the efficiency of photoetching or photoactivation and degradation are also likely to be affected by the surface composition and passivation of nanoparticles [28].…”
Section: Introductionmentioning
confidence: 98%